Apple and annie, the hamster duo ebook - Florence, Debbi Michiko (My Furry Foster Family, 2019)
Annie and Apple are a pair of chatty, restless dwarf hamsters from the animal shelter who are being fostered by eight-year-old Kaita Takano and her family. Kaita can't wait to find forever homes for the inquisitive furballs—but first, she has to find them! Bright, engaging illustrations and 1st-person narration invite early chapter-book readers into the nonstop fun and adventure.